3x-6-5x=9+7

Simple and best practice solution for 3x-6-5x=9+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x-6-5x=9+7 equation:


Simplifying
3x + -6 + -5x = 9 + 7

Reorder the terms:
-6 + 3x + -5x = 9 + 7

Combine like terms: 3x + -5x = -2x
-6 + -2x = 9 + 7

Combine like terms: 9 + 7 = 16
-6 + -2x = 16

Solving
-6 + -2x = 16

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '6' to each side of the equation.
-6 + 6 + -2x = 16 + 6

Combine like terms: -6 + 6 = 0
0 + -2x = 16 + 6
-2x = 16 + 6

Combine like terms: 16 + 6 = 22
-2x = 22

Divide each side by '-2'.
x = -11

Simplifying
x = -11

See similar equations:

| 4+5q=14 | | 7c*7e= | | x^2-24x+144=49 | | 100=x+0.2x | | 8-x=x+10 | | 3x-6-5=9+7 | | 2x+8=4x-18 | | x+x+1+x+2+x+3=30 | | x-(-5)=3 | | n+n+2+n+4=66 | | (18x-8)=(6x+4) | | 8(x-3)=23-2x | | 7x-(x-3)=6 | | .5(b)(2b+8)=21 | | 2g+4(3-g)=5g+19 | | x+x+1+x+2+x+3=-15 | | 4x+25=2x+49 | | 4x+36y=-12graph | | 2x+8(x-2)=4x-3(3-2x)-7 | | 3+3x=-7+x | | 6x-3(2x-4)+1=13 | | 15-4x+30=7-x | | 4+12+x=4+6+2x | | -0.01x^2+1.8x-106=0 | | 3+55x=33x+9 | | 4x+7=6x-19 | | (5y+9)+y= | | 11.8-0.4x+3.6=40 | | 25-2(4x+15)=51 | | -13+2x=-39+24x | | 25.00(x+5.00)=425.00 | | 5000=150+400 |

Equations solver categories